Nanoimprint Lithography of Al Nanovoids for Deep-UV SERS - Ding, Tao (ACS Appl Mater Interfaces, 2014)
[Image: see text] Deep-ultraviolet surface-enhanced Raman scattering (UV-SERS) is a promising technique for bioimaging and detection because many biological molecules possess UV absorption lines leading to strongly resonant Raman scattering. Here, Al nanovoid substrates are developed by combining nanoimprint lithography of etched polymer/silica opal films with electron beam evaporation, to give a high-performance sensing platform for UV-SERS. Enhancement by more than 3 orders of magnitude in the UV-SERS performance was obtained from the DNA base adenine, matching well the UV plasmonic optical signatures and simulations, demonstrating its suitability for biodetection.